Multiple dimensions of functional diversity affect stream fish taxonomic β‐diversity. (26th December 2022) - Bower, Luke M.; Stoczynski, Lauren; Peoples, Brandon K.; Patrick, Christopher J.; Brown, Bryan L.
Abstract: When investigating metacommunity dynamics, functional differences among species are often assumed to be as important as environmental differences between sites in determining β‐diversity. However, few studies have examined the influence of functional diversity on β‐diversity. We examine the relative importance of regional functional diversity partitioned by niche dimensions and environmental variation in structuring taxonomic β‐diversity of stream fishes using a large dataset of stream fish assemblages (hereafter, simply β‐diversity). We predicted that both functional diversity and environmental variation play a role in determining β‐diversity. We tested this prediction by modelling the patterns of stream fish β‐diversity as a function of environmental variation, functional diversity and γ‐richness across 10, 220 sites for 329 fish species using a series of conceptual path models. Environmental variation consistently affected β‐diversity across all models, whereas functional diversity and γ‐richness influenced β‐diversity only in some models. We show that including relevant trait differences among species in path models can improve their ability to explain β‐diversity, suggesting that functional traits influence β‐diversity. The ability of path models to explain β‐diversity varied depending on the trait grouping included in the model, demonstrating that specific path models representing different niche dimensions can improve the ability of a model to explain β‐diversity. In addition, parsing traits into different niche dimensions revealed alternative patterns of functional diversity–β‐diversity relationships that otherwise would have been missed. The selection of relevant traits and linked niche dimensions is critical for detecting relationships between functional diversity and β‐diversity. Using traits associated with different niche dimensions allows for the identification of niche dimensions most strongly associated with species sorting and the detection of patterns missed by focusing on a single niche dimension. Determining the niche dimensions that influence β‐diversity could provide insights into the processes driving biodiversity and metacommunity dynamics, improving our ability to conserve or restore aquatic communities.